Early rheumatoid arthritis - P. Sarzi-Puttini; F. Atzeni (PAGEPress Publications, 2011)
Rheumatoid arthritis (RA) is a systemic disease characterized by chronic inflammation of the synovial joints damage and loss of the function. The ultimate goal in managing RA is to prevent joint damage and to maintain functional ability. Consequently, early diagnosis and treatment is important, but predictive markers for RA are still confined to auto- antibodies and also magnetic resonance imaging (MRI) and sonography do not appear to sufficiently distinguish between early RA and non RA. Evidence shows that substantial and irreversible joint damage already occurs within the first 2 years after disease onset. This "window of opportunity" hypothesis for therapeutic intervention in RA is based on the existence of a time frame within which there is a potential for a greater response to therapy, resulting in sustained benefits or, perhaps most important, a chance of cure. There is increasing evidence for beneficial effects of early DMARDs (disease-modifying anti-rheumatic drugs) therapy over delayed treatment in patients who present with arthritis of recent onset. However, no universal consensus exists concerning the choice of initial drug or whether single drug or combination should be given as initial treatments. Most studies demonstrated superiority of aggressive over conventional approaches. Because the tumor necrosis factor (TNF)-α inhibitors have proved to stop joint damage progression in severe progressive RA, the achievement of these agents in early RA are currently of great interest.